Does maturity level influence the use of agile UX methods by digital startups? Evaluating design thinking, lean startup, and lean user experience - Henrique Lermen, Fernando (2022)
Context: Agile UX methods such as Design Thinking, Lean Startup, and Lean User Experience have been employed to deliver customer value and improve organizational performance. However, there is a lack of studies that assess how these tools are used at different stages of maturity of digital startups. Objective: The present study aims to compare the knowledge of graduated, incubated, and pre-incubated digital startups at university incubators concerning the use of Agile UX methods so that weaknesses and opportunities can be identified to provide co founders and scholars with new strategic insights. Method: Six reduced focus groups were conducted with 14 members of the six selected startups via multiple case studies. Answers were registered by researchers and then analyzed using an inductive process and codification. Results: The results indicated that digital startups had contact with consumers through market research, viability analysis, and product discontinuity. However, except for one startup, deficiencies in co-founders’ participation throughout developing products and services projects were identified. As far as the multiple case studies are concerned, Design Thinking and Lean Startup were employed by four of the startups, while two of them used the Lean User Experience method due to its higher maturity level. Conclusion: Although all Agile UX methods were employed, all six digital startups reported having made adaptations to the methods or to have used them only partially. Finally, it was concluded that the maturity level influences the Agile UX methods of each digital startup according to its nature and its stage of development in the market.